ARTICULATE STORYLINE MEDIA FOR CREATIVE THINKING OF LEARNERS ON HUMAN RESPIRATORY SYSTEM MATERIAL IN ELEMENTARY SCHOOL - Daniaty SR Danial; Ghullam Hamdu; Syarip Hidayat (Universitas Majalengka, 2025)
This research aims to analyze the effectiveness of Articulate Storyline media on the human respiratory system material in Class V of SDN 3 Sukamenak. This study employs a qualitative approach with a Design-Based Research (DBR) method. Data collection techniques include observation, interviews, and questionnaires. The study involved 1 material expert and 1 media expert as validators, 1 classroom teacher as a respondent, and 31 fifth-grade students as participants. The results of the material expert validation showed a percentage of 94.05% in the